2008
DOI: 10.1111/j.1559-1816.2008.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Memories of “Bad” Days Are More Biased Than Memories of “Good” Days: Past Saturdays Vary, but Past Mondays Are Always Blue

Abstract: In a survey of 202 participants, Monday was cited most frequently as the worst morning (65%) and evening (35%); whereas Friday (43%) and Saturday (45%) were the best evening and morning, respectively. Test–retest reliability was higher for worst morning (.89) and evening (.83) judgments, compared to best morning (.44) and evening (.61) judgments. In a second survey of 353 participants, ratings of typical moods were lowest on Monday, rising to a peak on Saturday, but actual momentary moods showed little or no v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 74 publications
(83 reference statements)
0
21
1
Order By: Relevance
“…), but remember a highly positive trip; this has been termed the “rosy view” phenomenon (Mitchell et al, 1997). A similar phenomenon holds for individuals’ beliefs about how negative events like menstruation (McFarland, Ross, & DeCourville, 1989) or the experience of Mondays (Stone, Hedges, Neale & Satin, 1985; Areni & Burger, 2008) will make us feel. We expect these experiences to be very negative, experience them as less negative than we anticipated, but remember them as more negative than they actually were.…”
Section: Effect Of Emotion and Emotional Goals On Autobiographicalmentioning
confidence: 76%
“…), but remember a highly positive trip; this has been termed the “rosy view” phenomenon (Mitchell et al, 1997). A similar phenomenon holds for individuals’ beliefs about how negative events like menstruation (McFarland, Ross, & DeCourville, 1989) or the experience of Mondays (Stone, Hedges, Neale & Satin, 1985; Areni & Burger, 2008) will make us feel. We expect these experiences to be very negative, experience them as less negative than we anticipated, but remember them as more negative than they actually were.…”
Section: Effect Of Emotion and Emotional Goals On Autobiographicalmentioning
confidence: 76%
“…A population-based study demonstrated that Monday mornings and evenings were indicated to be "the worst" in terms of stress 34. Stress scores were higher on workdays than on weekends, with the score increasing on Mondays after the weekend lows 25.…”
Section: Discussionmentioning
confidence: 99%
“…A number of 'happiness' studies focus on calendar regularities, which are of particular interest, not least because individuals have a clear separation between working days and weekends that affect their mood, social life and work-related stress (Yang et al, 2001;Areni and Burger, 2008). Using British Household Panel Survey (BHPS) data, Taylor (2006) finds that reported mental well-being is lower on Sundays for women, while job satisfaction is higher on Fridays and Saturdays.…”
Section: Introductionmentioning
confidence: 97%